Late Triassic high-Mg andesite/dacite suites from northern Hohxil, North Tibet: Geochronology, geochemical characteristics, petrogenetic processes and tectonic implications - Wang, Q.; Li, Zheng-Xiang; Chung, S.; Wyman, D.; Sun, Y.; Zhao, Z.; Zhu, Y.; Qiu, H. (Elsevier BV, 2011)
This study reports age, petrologic and geochemical data for andesites and dacites from the Late Triassic sedimentary strata of northern Hohxil, in the Hohxil–Songpan–Ganzi Block (northern Tibet), which constitutes the most voluminous Triassic strata on Earth. LA-ICP-MS zircon U-Pb analysis of dacite (210.4±1.9 Ma) and whole rock 40Ar–39Ar analyses for both the andesites and dacites (211±2 Ma and 210.9±1.6 Ma) show that the rocks were almost contemporaneous. Both rock types are sodium-rich and calc-alkaline. The andesites, characterized by high MgO (up to 10 wt.%) or Mg* (~70), TiO2, Al2O3, Cr, Ni, La/Yb and Th/La, but low Nb/Ta ratios, are geochemically similar to sanukitoids in southeastern Japan. The dacites are strongly peraluminous, and have high Al2O3 and La/Yb, low Y and Yb, coupled with negligible to positive Eu and Sr anomalies, comparable to slab-derived adakites in the circum Pacific arc system. Both rocks exhibit strongly fractionated platinum group element patterns, with Pt/Pt* (Pt anomaly), (Pt/Ir)N and Re/Os ratios higher than those of the primitive mantle. They have uniformly low εNd(t) values (-7.57–-9.59) and high (86Sr/87Sr)i ratios (0.7086–0.7106) that imply a continental rather than oceanic type magma source. We suggest that the northern Hohxil dacites were produced by partial melting of subducted sediments on the northward-subducting Songpan–Ganzi oceanic slab, and the high-Mg andesites were formed by subsequent interaction between the sediment-derived melts and mantle wedge peridotites. Taking into account the Triassic magmatic record from nearby regions, we suggest that the Late Triassic high-Mg andesite/dacite suites of northern Hohxil were generated in a forearc setting, and propose that double-sided subduction eventually closed the Songpan–Ganzi ocean during the Late Triassic.